The Analisis Hubungan Aktivitas Fisik dengan Kejadian Hipertensi pada Populasi Lansia - Candra, Agustin Marcela; Erjinyuare Amigo, Thomas Aquino; Wulandari, Riski (I Care Jurnal Keperawatan STIKes Panti Rapih, 2025)
Background: Elderly individuals are more susceptible to degenerative diseases such as heart disease, diabetes mellitus, and hypertension. Hypertension in the elderly is caused by changes in blood pressure related to aging and lifestyle factors, such as a lack of physical activity. Objective: This study aims to determine the relationship between physical activity and the incidence of hypertension in the elderly in the working area of Puskesmas Bantul II, Yogyakarta. Method: The study employed a quantitative method with a descriptive correlational design and a cross-sectional approach. The research was conducted at Puskesmas Bantul II, Yogyakarta, in June 2024. The study population consisted of elderly individuals aged ≥ 60 years, with a total sample size of 94 respondents selected using accidental sampling. The research instrument used was the Global Physical Activity Questionnaire (GPAQ). Results: The study results showed that, based on the incidence of hypertension, the majority of hypertensive elderly individuals engaged in light physical activity (78.0%, 32 respondents), while the majority of non-hypertensive elderly individuals engaged in vigorous physical activity (55.9%, 19 respondents). Statistical analysis using the Chi-Square test yielded a p-value of 0.002, indicating a significant relationship between physical activity and the incidence of hypertension in the elderly. Conclusion: Elderly individuals who engage in light physical activity have a higher risk of developing hypertension compared to those who engage in moderate or vigorous physical activity. It is important to educate the elderly on the benefits of regular physical activity to reduce the prevalence of hypertension.